2008
DOI: 10.1158/0008-5472.can-08-0132
|View full text |Cite
|
Sign up to set email alerts
|

Met and c-Src Cooperate to Compensate for Loss of Epidermal Growth Factor Receptor Kinase Activity in Breast Cancer Cells

Abstract: Breast cancers are not responsive to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKI), although 30% of breast cancers overexpress EGFR. The mechanism of intrinsic resistance to EGFR TKIs in breast cancer is the focus of current studies. Here, we observed that EGFR remains tyrosine phosphorylated in breast cancer cells that proliferate in the presence of EGFR TKIs. In one such cell line, SUM229, inhibiting c-Src kinase activity with either a dominantnegative c-Src or a c-Src TKI decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(121 citation statements)
references
References 48 publications
(58 reference statements)
6
115
0
Order By: Relevance
“…ErbBs are implicated in promoting proliferation and survival, and Met has important roles in cell motility and epithelial/mesenchymal transition. Our identification of ErbB and Met signalling in a single lung cancer cell line, and the involvement in responsiveness to ErbB and Met inhibitors is consistent with other recent studies that highlighted functional cooperation between these two receptor families (Bean et al, 2007;Guo et al, 2008;Mueller et al, 2008;Shattuck et al, 2008;Yano et al, 2008). Interaction of these receptor families has been suggested for years, based on the finding that Met is often co-overexpressed with ErbBs in prostate and breast carcinoma.…”
Section: Discussionsupporting
confidence: 90%
“…ErbBs are implicated in promoting proliferation and survival, and Met has important roles in cell motility and epithelial/mesenchymal transition. Our identification of ErbB and Met signalling in a single lung cancer cell line, and the involvement in responsiveness to ErbB and Met inhibitors is consistent with other recent studies that highlighted functional cooperation between these two receptor families (Bean et al, 2007;Guo et al, 2008;Mueller et al, 2008;Shattuck et al, 2008;Yano et al, 2008). Interaction of these receptor families has been suggested for years, based on the finding that Met is often co-overexpressed with ErbBs in prostate and breast carcinoma.…”
Section: Discussionsupporting
confidence: 90%
“…EGFR and/or ErbB2, Met, PDGFR, IL-6R) in solid malignant tumors results in redundant inputs that drive downstream signaling, therefore limiting the effectiveness of therapies that target just a single receptor tyrosine kinase [207] . For example, Met/c-Src signaling has been recently shown to mediate EGFR tyrosine phosphorylation and cell growth in cultured SUM229 breast cancer cells in the presence of EGFR-TKIs [208] . Presently, there is no uniform set of biomarkers that can be used to accurately predict a therapeutic response in solid tumors, including intrahepatic cholangiocarcinoma, to ErbB-directed therapies.…”
Section: Factors Affecting Therapeuticmentioning
confidence: 99%
“…Src is involved in the crosstalk between many signaling pathways, including the integrin/FAK, EGF receptor (EGFR), Ras/Raf/MEK, PI3K/AKT, and JAK/STAT pathways, which promote cell proliferation, adhesion, invasion, migration, metastasis, and tumorigenesis (1,2). A previous analysis found that 20% of human breast cancers overexpress both Src and EGFR, suggesting the involvement of Src in the EGFR signaling pathway (3). Another study found that Src activation is required for EGF-induced integrin-mediated migration and metastasis.…”
Section: Introductionmentioning
confidence: 99%